2009
DOI: 10.1002/lt.21786
|View full text |Cite
|
Sign up to set email alerts
|

Long-term management after liver transplantation: Primary care physician versus hepatologist

Abstract: As long-term survival after liver transplantation increases, metabolic complications are becoming increasingly prevalent. Given concerns about which group of providers should be managing liver recipients and how well metabolic complications are managed, we administered a postal survey to 280 transplant hepatologists to determine attitudes, perceptions, and practice patterns in the management of metabolic complications after transplantation. The response rate was 68.2%. There was great variation in patterns of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…The rates of being up-to-date for SOTR varied with time since transplantation; however, at no point were the rates in this group as high as that reported in the general population of Ontario during this time period (40). Chan (45,46). patients with obesity and diabetes) (41), the screening uptake in SOTR is lower than that observed in these populations (42)(43)(44).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The rates of being up-to-date for SOTR varied with time since transplantation; however, at no point were the rates in this group as high as that reported in the general population of Ontario during this time period (40). Chan (45,46). patients with obesity and diabetes) (41), the screening uptake in SOTR is lower than that observed in these populations (42)(43)(44).…”
Section: Discussionmentioning
confidence: 67%
“…Although there is evidence that cancer screening rates are reduced in patients with other chronic diseases (e.g. However, the survey also reported that the majority of hepatologists felt that the involvement of PCP occurred infrequently and only 35.8% were satisfied with the PCPs' level of involvement (45). Chan (45,46).…”
Section: Discussionmentioning
confidence: 94%
“…Questions were adapted from earlier validated surveys when available. 10, 12, 13 After initial development, the survey was pretested among seven physicians with hepatology expertise and experience with HCV treatment, with each provider completing a cognitive interview about the survey.…”
Section: Methodsmentioning
confidence: 99%
“…[3][4][5][6] Many centers defer the management of metabolic syndrome and medical complications to primary care physicians. 7 Table 1 summarizes the most common metabolic complications after OLT, and these complications are discussed in greater detail later in this article.…”
mentioning
confidence: 99%